2008
DOI: 10.1021/nn800020h
|View full text |Cite
|
Sign up to set email alerts
|

2D Self-Bundled CdS Nanorods with Micrometer Dimension in the Absence of an External Directing Process

Abstract: In the absence of an external direction-controlling process, exclusive self-bundled arrays of CdS nanorods are formed using a facile solution-based method involving trioctylphosphine (TOP) and tetradecylphosphonic acids (TDPA) as cosurfactants. CdS self-bundled arrays with an area of as large as 2.0 microm(2) could be obtained. A detailed mechanistic investigation leads us to conclude that the matching in nanorod concentration, intrinsic properties of CdS, and the hydrocarbon chains of the surfactants between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 40 publications
2
62
0
Order By: Relevance
“…[28] Even without electric field, ordering is possible if surfactants with three or four alkane chains were used for the stabilization of CdS which facilitate corralling by hydrocarbon interaction. [29] Above a critical particle concentration, simple drying led to 2D mesocrystals.…”
Section: Ordering By Physical Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…[28] Even without electric field, ordering is possible if surfactants with three or four alkane chains were used for the stabilization of CdS which facilitate corralling by hydrocarbon interaction. [29] Above a critical particle concentration, simple drying led to 2D mesocrystals.…”
Section: Ordering By Physical Fieldsmentioning
confidence: 99%
“…Upon capping CdS with tri-n-octylphosphine (TOP) and tetradecylphosphonic acid (TDPA), they obtained 2D self-bundled CdS nanorods with an area as large as 2.0 mm 2 . [29] TEM studies revealed self-assemblies of CdS nanorods with outer edges of leaning bundles and an inner part of hexagonal packing perpendicular to the substrate. Evaporation-induced corralling of nanorods normal to the substrate, might serve as a nucleation site.…”
Section: Mesocrystals Formed By Cds/cdse Nanorodsmentioning
confidence: 99%
“…[3,4] Due to their structural nature, the mesoscopically well-ordered crystals can exhibit unique properties and functionalities that cannot be seen in the parent bulk materials. Typical examples of mesocrystals can be found in various materials as diverse as metal oxides, [5][6][7][8][9] II/IV semiconductors, [10,11] complex oxides, [12,13] fluorides, [14] phosphates, [15] organic molecular systems, [16,17] etc. To date, considerable efforts have been made to develop synthesis mechanisms, to acquire new members of the mesocrystal family, and to tailor their tantalizing functionalities.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] Nanorods have been directed into perpendicularly ordered assemblies either by using external electric fields or by evaporation control at solid/liquid or liquid/air interfaces. [11][12][13][14] The aspect ratio and polydispersity of the rods in addition to solvent-evaporation dynamics plays a key role in achieving vertical alignment and close packing from solution. In effect, the gradual packing of randomly dispersed nanorods into a reducing solvent volume allows attractive dipole-dipole and Van der Walls forces between ligand capped nanorods to dominate the assembly behaviour at a substrate.…”
Section: Introductionmentioning
confidence: 99%